Formulasi dan Evaluasi Tablet Floating furosemida Gastroretentif Menggunakan Kitosan Dari Cangkang Keong Mas (Pomacea canaliculata) - Setiawan, Iwan; Hartono (Jurnal Farmasi (Journal of Pharmacy), 2015)
Chitosan is kind of a natural polymer which is a product of deacetylation of chitin which can be obtained from the shells of golden snails (Pomacea canaliculata). Gastroretentive drug delivery systems can help improve the bioavailability, can maintain contact time of the drug longer with the gastrointestinal mucosa cause bioavailability of the drug will be higher, the efficacy of therapy, reducing the time interval of drug administration, reduce therapeutic doses and will ultimately improve patient compliance. The objective of the present study was to develop and evaluate gastroretentive floating tablet of furosemida using chitosan of shell golden snails. Chitosan which is isolated from the shells of snails formulated as polymer concentration variation in the formula of making floating tablets furosemide. The results showed shells of snails obtained from chitosan yield of 10.8%. Furosemide tablets containing chitosan polymers produce good powder and meets the requirements include the flow time, angle of repose and compressibility index, uniformity of weight, hardness, friability and disintegration time. The Formulation F3 containing (Furosemide with the highest concentration of chitosan) was found to the best. The test results mainly floating tablet hardness and Buoyancy / floating test showed significantly different results with furosemide tablets containing no polymer chitosan. This suggests that the natural polymer chitosan derived from the shells of golden snails are potentially as the building blocks of making tablets with gastroretentive drug delivery systems.